A Classification of Clay‐Rich Subaqueous Density Flow Structures. Issue 5 (7th May 2018) - Hermidas, Navid; Eggenhuisen, Joris T.; Jacinto, Ricardo Silva; Luthi, Stefan M.; Toth, Ferenc; Pohl, Florian
Abstract : This study presents a classification for subaqueous clay‐laden sediment gravity flows. A series of laboratory flume experiments were performed using 9%, 15%, and 21% sediment mixture concentrations composed of sand, silt, clay, and tap water, on varying bed slopes of 6°, 8°, and 9.5°, and with discharge rates of 10 and 15 m 3 /hr. In addition to the characteristics of the boundary and plug layers, which have been previously used for the classification of open‐channel clay‐laden flows, the newly presented classification also incorporates the treatment of the free shear layer. The flow states within the boundary and free shear layers were established using calculation of the inner variable, self‐similarity considerations, and the magnitude of the apparent viscosity. Based on the experimental observations four flow types were recognized: (1) a clay‐rich plug flow with a laminar free shear layer, a plug layer, and a laminar boundary layer, (2) a top transitional plug flow containing a turbulent free shear layer, a plug layer, and a laminar boundary layer, (3) a transitional turbidity current with a turbulent free shear layer, no plug layer, and a laminar boundary layer, and (4) a fully turbulent turbidity current. A connection between the emplaced deposits and the relevant flow types is drawn and it is shown that a Froude number, two Reynolds numbers, and a dimensionless yield stress parameter are sufficient to associate an experimental flow type with a natural large‐scale density flow. Plain Language Summary: Deposits of submarine density flows can be important hydrocarbon reservoirs. Quality of these reservoirs is primarily controlled by grain size and clay concentration of the sediment mixture at the time of deposition. These parameters are dictated by the structures of the sediment carrying flow at the time of deposition. This study proposes a classification for muddy subaqueous density flows based on the flow structures. According to this classification a clay‐rich flow may fall within one of four distinct flow types: (1) a cohesive plug flow with laminar free shear and boundary layers and a plug, (2) a top transitional plug flow containing a turbulent free shear layer, a plug layer, and a laminar boundary layer, (3) a transitional turbidity current with a turbulent free shear layer and a laminar boundary layer, and (4) a turbulent turbidity current. A connection between the emplaced deposit and the relevant flow type is drawn through the results obtained from flume experiments. It is proposed that a Froude number, a boundary layer Reynolds numbers, a free shear layer Reynolds number, and a dimensionless yield stress parameter are sufficient to connect a flow type with a natural large‐scale density flow. Key Points: Four distinct flow structures for muddy density flows were observed Dependence of the deposit emplaced by a subaqueous density flow on its flow structure was examined Upscaling of small flume experiments to large-scale natural density flows was investigated